"LLPS; the business autobots" special reference to the limited liability partnerships (Malaysia) consultative document April 2008 - Abd Ghadas, Zuhairah Ariff (Malaysian Association of Company Secretaries, 2010)
Generally, there are three common business vehicles which are used to "mobilize" trade all over the world; the sole proprietorships, partnerships and companies. Nonetheless, in many countries, business vehicles have been developed to include more option other than these three conventional structures. It is observed that development and expansion of business structures in all countries are made to cater business practices; both local and international, to maximize the benefit of the taz regime and to comply with respective laws and regulation. This paper intends to highlight features of one of the latest creation of business entities; Limited Liability Partnerships (LLPs). Despite its name, LLP is neither a partnership nor a company. It is a totally new business vehicle with hybrid attributes. In Malaysia, the Companies Commision Malaysia (CMM) had twice published the consultation document on Limited Liability Partnerships (LLP), the first one in 2003 and the second one in April 2008. This article highlights certain features of Malaysian LLP as proposed by the CCM.